2019
DOI: 10.1108/ijm-11-2017-0314
|View full text |Cite
|
Sign up to set email alerts
|

Do vocational high school graduates have better employment outcomes than general high school graduates?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 52 publications
1
14
0
1
Order By: Relevance
“…Our findings are supported from previous literature for example , Funkhouser, 2006;Jadotte, 2009;Kemal & Naci, 2009;Fuchs, Kubis, &Schneider, 2016 andSefiddashti et al, 2016. Technical/vocational trainings is most often perceived to increase the labor market opportunities for youth (Malamud & Pop-Eleches;2010) and marginalized groups including less educated women. The found impact of training is to be positive on labor market activities, (Aslam & Rawal, 2013;Torun & Tumen, 2017). Our study also supports this notion.…”
Section: The Estimation Results Of Binary Probit Modelsupporting
confidence: 85%
“…Our findings are supported from previous literature for example , Funkhouser, 2006;Jadotte, 2009;Kemal & Naci, 2009;Fuchs, Kubis, &Schneider, 2016 andSefiddashti et al, 2016. Technical/vocational trainings is most often perceived to increase the labor market opportunities for youth (Malamud & Pop-Eleches;2010) and marginalized groups including less educated women. The found impact of training is to be positive on labor market activities, (Aslam & Rawal, 2013;Torun & Tumen, 2017). Our study also supports this notion.…”
Section: The Estimation Results Of Binary Probit Modelsupporting
confidence: 85%
“…As to the impact of migration on the employment status of women, it is found that migration is only significantly affecting women's employment status when women are working either as OAW or CFW (Fuchs et al 2016;Sefiddashti et al 2016). On similar lines, we see that technical/vocational training positively affects the choice of any employment status of a woman (Aslam and Rawal 2013;Torun and Tumen 2019). Compared to not working women, household size negatively affects the women's choice of opting for any employment status except for CFW in our selected sample (Usman and Sanusi 2016).…”
Section: Discussion and Findingsmentioning
confidence: 55%
“…12 That is, vocational education as such may not be enough. A study in Turkey(Torun and Tumen 2019), for instance, shows that for an individual who pursues a high school degree and does not aim for college education, vocational education does not increase employment prospects relative to general education.13 Of course, another important argument could be that on-the-job training provides better job-specific training than classroom training.…”
mentioning
confidence: 99%